Antigen array and diagnostic uses thereof (2005)
A method of diagnosing an immune disease, or a predisposition thereto, in a subject is disclosed. The method comprises determining a capacity of immunoglobulins of the subject to specifically bind each antigen probe of an antigen probe set, wherein the antigen probe set comprises a plurality of antigen probes selected from the group consisting of at least a portion of a cell/tissue structure molecule, at least a portion of a heat shock protein, at least a portion of an immune system molecule, at least a portion of a homopolymeric polypeptide, at least a portion of a hormone, at least a portion of a metabolic enzyme, at least a portion of a microbial antigen, at least a portion of a molluscan antigen, at least a portion of a nucleic acid, at least a portion of a plant antigen, at least a portion of plasma molecule, and at least a portion of a tissue antigen, wherein the capacity is indicative of the immune disease or the predisposition thereto, thereby diagnosing the immune disease, or the predisposition thereto, in the subject.